PENGARUH TERAPI BERMAIN ALAT KEDOKTERAN TERHADAP PERILAKU KOOPERATIF DALAM ASUHAN KEPERAWATAN ANAK USIA PRA SEKOLAH DI RUANG ANAK RSUD KEFAMENANU KABUPATEN TIMOR TENGAH UTARA: Therapeutic Effect of Playing With Medical Tool Against Cooperative Behavior Preschooler (3-5 Years) During Hospitalization in Children's Hospital Space Kefamenanu Timor Tengah Utara - FLORENTIANUS TAT; SELFIANA A. SING (Research and Community Service Unit, Politeknik Kesehatan Kemenkes Kupang, 2014)
Playing medical instrument therapy an example of playing therapy done before implementasi the nurse activity. Introducting the medical interment to children will make them more comfortable that can infl ill the cooperative behavior to their nurse. The aim of this research is to know the impact of playing medical intrument therapy to wards. Clidren,s cooperative behavior in children of pre-school (3 – 5 years old) during the hospitalization in cihildrent room RSUD Kefamenanu. To design this research, the researcher uses one group pre test – post test. The sampel of this research is 32 respondents. The needed data is collcted by observing cooperatitive behavior of children before andf after giving the therapy. To know the different of childrens cooperative behavior before and after going the playing therapy, Wilcoxon test is used. Based on the Wilcoxon analysis, the cooperative level shows value of p = 0,000 (<0,005). Based on the result, it can be conluded that there is an impcict of playing medical instrument to ward the level cooperative level of children in pre – school (3 – 5 tahun) during the hospitalization in Childrens room RSUD Kefamenanu.